2011
DOI: 10.1139/y11-023
|View full text |Cite
|
Sign up to set email alerts
|

Orchidectomy attenuates impaired endothelial effects of a high-salt diet in Sprague–Dawley rats

Abstract: The effect of sex hormones on vascular reactivity is considered one of the underlying factors contributing to gender differences in cardiovascular functions and diseases. Experiments were designed to investigate the role of androgens in salt-induced hypertension by assessing the relaxation response of isolated aortic rings to acetylcholine and sodium nitroprusside in the presence or absence of l-nitroarginine methyl ester in Sprague-Dawley rats. The rats were either orchidectomized or sham-operated, with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 35 publications
5
25
1
Order By: Relevance
“…These findings are consistent with our previous report which showed that testosterone promoted impaired reactivity of aortic rings from male Sprague-Dawley rats fed a HSD. 10 Attenuation by orchidectomy of the elevated RVR observed in rats fed HSD suggests that testosterone did not only promote BPelevating effect of a HSD, but may also enhance the impairment of renovascular function that could be present in rats fed a HSD. Renovascular dysfunction is associated with enhanced renal vasoconstriction, decreased renal blood flow and in some cases, increased plasma volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with our previous report which showed that testosterone promoted impaired reactivity of aortic rings from male Sprague-Dawley rats fed a HSD. 10 Attenuation by orchidectomy of the elevated RVR observed in rats fed HSD suggests that testosterone did not only promote BPelevating effect of a HSD, but may also enhance the impairment of renovascular function that could be present in rats fed a HSD. Renovascular dysfunction is associated with enhanced renal vasoconstriction, decreased renal blood flow and in some cases, increased plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…16 We have previously demonstrated that testosterone increases vascular reactivity of the aorta from male rats fed a HSD. 10 But effects of testosterone on arterioles are yet to be fully understood considering the importance of arterioles in the overall systemic vascular resistance and regulation of BP under normal and pathological conditions. Salt sensitivity exhibits sexual dimorphism with male rats developing higher BP compared to female rats when fed a HSD.…”
mentioning
confidence: 99%
“…Ltd., Bangalore, India) that already contained 0.3% NaCl, to give 8% NaCl (Adegunloye and Sofola 1997). All of the rats that underwent surgery received an injection of penicillin (300 000 IU/kg body mass) at the time of surgery to prevent infections, and were allowed a 3 day recovery period before the beginning of the experiments (Oloyo et al 2011a). After recovery from anesthesia, all animals were returned to their cages.…”
Section: Methodsmentioning
confidence: 99%
“…One of the mechanisms by which a high-salt diet induces hypertension includes impairment of vascular functions (Oloyo et al 2011a). For instance, increased dietary salt intake has been demonstrated to impair the relaxation response to vasodilator agents in several vascular beds in laboratory animals (Zhu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Vascular function impairment is known to be part of the key mechanisms by which high-salt diet leads to the increase in blood pressure. [5][6][7] In the endothelial cells, endothelial nitric oxide synthase (eNOS) helps in the production of citrulline and nitric oxide from l-arginine. 8 The eNOS mRNA expression has, however, been reported to be a key modulator of vascular tone, and its uncoupling has been shown to contribute to development of hypertension.…”
Section: Introductionmentioning
confidence: 99%